Construção de aprendizagem : aplicação da geometria descritiva espacial e desenho técnico básico como ferramenta de ensino - Nascimento, Raquel Pereira do (2015)
This work is the result of a research that aimed to assist the process of teaching and learning in their curricular content. Thus a literature of historical study on the teaching of geometry and their contributions to learning was done. We report the activities of application experience in three high school classes at the State School Vila Rica. Therefore, the records made, based on the theoretical studies, intend to bring a re ection of teachers as Geometry can be used as support for education, so that the spatial visualization is a tool to support and serve as a demonstration for the students in their practices. Based on this research, and in order to decrease the di culties related to spatial knowledge, we present a methodological proposal for dynamic application of high school content, using descriptive geometry in conjunction with the Technical Drawing. This methodology uses drawing as a teaching tool and building solid as a complement of manipulative activities. Soon we proposed a sequence of learning activities with increasing levels of di culty. The prospects of drawing and its projections enabled the students to develop skills to solve problems involving abstraction. This tool also allows for the use of intuition that helps to arouse the interest of students in geometric activities. The application of graphical representations allowed individuals to self analysis of their output, and to carry out the activities they re ected on their actions, a fact that arouses criticism. The search for innovation encourages students to researching consequently is given power for the student in decision-making. The results obtained are relevant to understanding the learning of the individual steps. According to the analysis of the results realized how methodologies that are distant mechanical teachings, contribute to student learning. The students participating in these activities showed a considerable improvement in spatial thinking and knowledge, so that increases the concepts studied during participation in the project contributed to the performance at the time of classes.